Characterization of β-adrenergic receptors in the heart chambers of adult turkeys. Issue 3 (June 2015) - Hoffmann, Sandra; Müller, Torsten; Abraham, Getu
Highlights: β-Adrenergic receptors are equally distributed in turkey hearts. β-Adrenergic receptor density is age-dependent. The β1 -adrenergic receptor subtype was exclusively present in all four cardiac chambers. Abstract: The presence, distribution and characteristics of chamber-specific β-adrenergic receptors in adult turkey hearts were investigated by radioligand binding studies using (−)-[ 125 I]-iodocyanopindolol (ICYP). The β1 -selective (CGP 20712A) and β2 -selective (ICI 118.551) antagonists as well as the nonselective β-agonists isoproterenol, epinephrine and norepinephrine were used in displacement studies. In all cardiac chambers, ICI 118.551 and CGP 20712A displacement curves were monophasic and steep, with the affinity of CGP 20712A higher than that of ICI 118.551, indicating the exclusive presence of the β1 -adrenergic receptor subtype. The agonist rank order of potency was isoproterenol > norepinephrine ≥ epinephrine, typical for the β1 -receptor subtype. In all chambers, the density of β-adrenergic receptors was ~40 fmol/mg protein and the KD was ~30 pM. The study revealed similar β-adrenergic receptor density mainly of the β1 -subtype in all cardiac chambers, indicating that this receptor subtype could contribute equally to regulate cardiac physiological function and pathophysiology.